Molecular Mechanisms of Leaf Morphogenesis - Koyama, Tomotsugu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Leaf morphology is obviously determined in a plant. By contrast, its morphology is often changeable when the plant copes with various environmental changes. To update our understanding of the regulatory mechanisms of leaf morphogenesis with robustness and flexibility, this book provides a series of academic papers that cover molecular mechanism of leaf morphogenesis and offers readers' opportunities to find beautiful mechanisms that plants develop.